Acute Hormonal and Blood Biochemistry Responses of Calves to Open Castration in Sokoto Gudali Breed of Cattle - Olaifa, A.K.; Adeleke, I.O. (Global Science Independent Journal, 2020)
Castration of cattle is common in modern veterinary practice with different motives and reasons. Castration has been observed to cause alterations in body system parameters with accompanying stress under various methods in farm animals. This study was aimed at evaluating the hormonal, hematological and biochemical responses to open castration in Sokoto gudali calves. Six calves were castrated using an open method using a sterile scalpel. Blood was collected at 30-minutes interval for 2 hours and assayed for hematological, biochemical and hormonal analyses. The present study showed that castration of calves caused a transient increase in packed cell volume, red blood cell count, white blood cell count, platelets, hemoglobin concentration and neutrophil at 30minutes post-castration and later decreased to nearly the initial levels. It decreased significantly (P<0.05) at 90min when compared with the 30min value. There were fluctuations in the estrogen, testosterone and cortisol levels while no significant changes in the electrolytes level was observed. The fluctuations in these parameters could be the result of the disruption in the testosterone production owing to the castration. It could therefore be concluded that open castration in calves using sterile scapel is safe and not detrimental to the physiology of the animals under study.